Dexterity testing and residents' surgical performance. - Kirby, T J (1979)
1. With some exceptions, those who choose ophthalmology as a career may approximate the general population in innate manual dexterity. 2. Many factors other than manual dexterity influence the development of surgical skills by residents. 3. If dexterity testing is to be used, the addition or inclusion of tests for spatial aptitudes may be more helpful than simple dexterity tests alone. The predictive value of such tests for surgical performance would need vertification. 4. The development of a special test directly related to handling surgical instruments, to cutting, and to sewing (the criteria) may be more practical than the ones used in this study.